Non-T-depleted haploidentical transplantation with post-transplant cyclophosphamide in patients with secondary versus de novo AML in first complete remission: a study from the ALWP/EBMT - Arnon Nagler; Myriam Labopin; Didier Blaise; Anna Maria Raiola; Lucia Lopez Corral; Stefania Bramanti; Simona Sica; Mi Kwon; Yener Koc; Jiri Pavlu; Alexander Kulagin; Alessandro Busca; et al. (Journal of Hematology & Oncology, 2023)
Abstract We compared outcomes of adult patients with secondary acute myeloid leukemia (sAML) versus de novo AML after non-T-depleted haploidentical stem cell transplant (HaploSCT) with post-transplant cyclophosphamide (PTCy). Seventeen hundred and eleven AML patients (sAML-231, de novo-1480) in first complete remission transplanted from 2010 to 2021, were included. Patients with de novo AML were younger, median age 55.8 versus 60.8 years, p < 0.0001, had better transplantation comorbidity index (HCT-CI) ≥ 3 21.3% versus 40.8%, p < 0.0001 and Karnofsky performance status (KPS) with KPS ≥ 90 in 78% versus 68.5%, respectively, p = 0.002. The two patient groups did not differ with respect to gender, cytomegalovirus serostatus, and cell source. Median time from diagnosis to HaploSCT was 5.2 versus 4.9 months, respectively, p = 0.005. Fewer sAML patients received myeloablative conditioning 35.1% versus 50.1%, p < 0.0001. Two hundred and eleven sAML and 410 de novo AML patients were included in the matched-pair analysis matching two de novo AML with each sAML. No significant difference was observed in any transplantation outcome parameter between the sAML versus de novo AML groups. Two-year non-relapse mortality and relapse incidence did not differ with HaploSCT for de novo versus sAML; 21.4% versus 21%, hazard ratio (HR) = 0.98, p = 0.9 and 23.4% versus 20.6%, HR = 0.92, p = 0.67, respectively. Two-year leukemia-free survival, overall survival, and graft-versus-host disease (GVHD)-free, relapse-free survival were also not different between the de novo AML and sAML groups 55.2% versus 58.4%, HR = 0.95, p = 0.67; 61.4% versus 66.4%, HR = 0.91, p = 0.51 and 46.3% versus 48.2%, HR = 0.92, p = 0.48, respectively. Similarly, the incidence of engraftment as well as acute and chronic GVHD was similar between the 2 cohorts. In conclusion, HaploSCT with PTCy may be able to overcome the bad prognosis of sAML as results are not significantly different to those of HaploSCT in de novo AML.